Membangun Relasi Dengan Ilahi: Proses Pencarian Dan Penemuan Kehadiran Tuhan - Karolus Teguh Santoso; Monica Innanda Chiaralazzo (Jurnal Magistra, 2024)
Building a relationship with God requires a balance between reason and faith. Although often perceived as contradictory, they complement each other. Humans, with their limited reasoning, can acknowledge the presence of God through the experience of faith. This process is not merely intellectual, but also involves the light of faith that enables one to feel God's presence in daily life. Spiritual quality is key in fostering an intimate relationship with God. Prayer, meditation, and adoration serve as means to enhance spiritual quality. The research methodology of this article employs the literature review method, presenting insights from various relevant sources on building a relationship with God. In conclusion, seeking and finding God necessitates a balance between reason and faith. Spiritual quality, theological perspectives, and embracing faith in Christ aid individuals in experiencing God's presence in their lives.